Designer's log in planning the development of comics with socioscientific issues content: Case studies - Fadhlan Muchlas Abrori; Adi Nur Cahyono; Zsolt Lavicza (Universitas Muhammadiyah Malang, 2024)
The development of learning media research evolves rapidly in design-based research (DBR). However, most of the research in this area concentrated on media implementation and media format. In this paper, we explain one side rarely discussed: the process of designing media pre-implementation. This research uses the designer’s log as core data that notes the essential things during the discussion between media designers and practitioners. This study depicts two case studies when researchers (as media designers) and teachers (as practitiones) were developing comics with socioscientific issues (SSI) content. This research employed a case studies approach, using the designer’s log in three meetings with teachers. The data analysis of the designer’s log focused on three criteria: analysis, comics-building, and teaching activities development. The main themes identified as results in this study were the student experience in comics, previous content related to SSI, comics form, SSI content in comics, and classroom activities. This study also presented designer log examples highlighting our discussion with teachers to explain teachers’ consideration in designing comics with SSI content. From this study, we offer recommendations, especially regarding DBR. Firstly, future researchers need to be aware not only of the final DBR product but also of the product design process; secondly, in preparing media (in this paper, comics), determining content needs to be considered together between designers and teachers from student conditions, culture, and school background.